Parental socioeconomic and educational level and chil overweight - lessons from a municipality based study - Silva, Ana Lúcia (2012)
INTRODUCTION: The prevalence of childhood obesity is rising rapidly in Portugal, reaching one of the worst positions in the European Union. Inadequate food habits with high intake of high energy dense foods, seems to be one of the main factor behind this epidemic. Family socioeconomic status also appears to be an obesogenic factor, particularly parents’ educational level and their income. To better understand the association of unbalanced dietary habits and socioeconomic environment on children nutritional status and to develop effective prevention strategies, are the main aims of this municipality study METHODS: A cross-sectional study was conducted on five municipalities (Viana do Castelo, Fundão, Oeiras, Seixal and Montijo), which included 3275 children (6-9 years old), attending the universe of public elementary schools. Childhood nutritional status was assessed by anthropometric parameters (weight and height) considering the CDC growthcharts criteria percentiles of BMI. Children’s food habits, socioeconomic condition and parent’s level education were collected by a family questionnaire. RESULTS: Prevalence of childhood overweight (BMI≥P85) was 32,1%, and over 14% of children were obese (BMI≥P95). Pre-obesity (P85≤ BMI< P95) prevalence was higher among girls (18,1%) than boys (17,8%). The consumption of fast food group and candies occurred mainly in every 15 days (48,4% and 35,5% respectively), pastry products showed a higher frequency of 1-3 times a week (41,5%). The percentage of children consuming vegetables, at least daily, varied with nutritional status: 23,0%; 25,7%; 26,2%; 21,0% in underweight, normal, pre-obese and obese children. Overweight was associated with parent´s low socioeconomic status, and middle parents educational level. CONCLUSION: Further careful analysis will help to better understand the role of obesogenic factors. This knowledge may identify additional potential effective interventions at local level in order to reverse the obesity trends in Portuguese children.